The influence of HIV infection and antiretroviral treatment on pulmonary function in individuals in an urban setting in sub-Saharan Africa - Oda E. van den Berg (AOSIS, 2021)
Background: With the roll-out of antiretroviral treatment (ART), the life expectancy of people with HIV and, hence, morbidity from non-communicable diseases, including pulmonary diseases, have increased.